(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2022)
This article presents a compilation of scholarly perspectives on environmental journalism, especially between 2010 and 2020. We begin from the standpoint and experience of non-Brazilian countries to notice changes that this field of knowledge has been going through in the international context. The goal is not only to reflect about the challenges faced by professionals working in this area, but also the interfaces between environmental journalism and other fields, such as economy and politics, and its characteristics in the current context. To guide our approach, studies by Pezzullo and Cox (2018), Hansen (2019), Takahashi and Meisner (2012), Druschke and McGreavy (2016), Boykoff (2011), Dotson et al. (2012), Willer and Takahashi (2018), Christians et al. (2009), and Williams (2017), among others, helped us construct this reflection.